2015
DOI: 10.1109/tps.2015.2452947
|View full text |Cite
|
Sign up to set email alerts
|

Study of Transient Spark Discharge Properties Using Kinetic Modeling

Abstract: The kinetic model simulating plasma chemistry induced by Transient Spark (TS) discharge in air is presented in this paper. TS is a dc-driven self-pulsing discharge of streamer-to-spark transition type. The presented kinetic model defines the temporal evolution of reduced electric field strength E/N, gas temperature, and density of neutrals N during the evolution of TS discharge, so that calculated electron density is in agreement with experimental results. We studied the mechanism of the streamer-to-spark tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 44 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…During the pulse-off time, negative voltage was observed because of the back electromotive force, but the reversed current was limited. Because of gas preheating and memory effect created by the previous discharge [44], the breakdown voltage of the next potential pulses is relatively lower, ranging from 1.25 to 1.5 kV. Similarly, the discharge current pulses are broader and smaller, ranging from 0.25 to 0.75 A (as presented in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…During the pulse-off time, negative voltage was observed because of the back electromotive force, but the reversed current was limited. Because of gas preheating and memory effect created by the previous discharge [44], the breakdown voltage of the next potential pulses is relatively lower, ranging from 1.25 to 1.5 kV. Similarly, the discharge current pulses are broader and smaller, ranging from 0.25 to 0.75 A (as presented in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…During the pulse-off time, no power pulses were observed. Because of the gas preheating and accumulated excited metastable species—e.g., O, O 2 (a 1 Δ g ), and N 2 (A 3 Σ), which were produced mainly by the first pulse—the next four transient spark discharge pulses could be generated using lower electrical power [44, 45]. However, the width of the latter four discharge pulses was observed to be broader than the that of the first pulse.…”
Section: Resultsmentioning
confidence: 99%
“…The timeresolved OES study and imaging of the TS revealed that the emission from the excited molecular nitrogen is generated mostly during the streamer phase, and the emission of the atomic lines comes mainly from the spark phase [42,43]. During the TS spark phase the heating of the gas up to 2000-3000 K was also observed, high electron density (= high degree of ionization) [44], and high degree of atomization [45]. We assume that the plasma generated by mini-GAD has similar chemical activity as the plasma generated during the spark phase of the TS discharge.…”
Section: Generation Of Reactive Species In Gaseous Phasementioning
confidence: 98%
“…The maximum current is approximately 100 mA. The electron density ranged , from 10 16 to 10 18 cm –3 . The research was carried out with constant discharge power (25 W) and total feed flow (1 mol/h).…”
Section: Methodsmentioning
confidence: 99%